A Meta-Analytical Approach to Cognize the Pooled Effect of Customer Relationship Management on Firm Performance - Das, Subhasish; Mohapatra, Amiya Kumar; Pandey, Shailesh; Nayak, Yayati (Indian Journal of Marketing, 2025)
Purpose : This study attempted to explore the pooled effect of customer relationship management (CRM) on firm performance with a meta-analytical approach. It aimed to provide a holistic view of how CRM practices influenced organizational performance. Methodology : The meta-analysis aggregated data from 51 studies with a total sample size of 11,081. This paper utilized the random effects model by taking into account the differences across studies in order to draw on the Z-values representing overall effect size, confidence levels, and p-values. Additionally, heterogeneity across the studies was quantified with the I² statistic and publication bias was examined with the Trim-and-Fill method. Findings : The results unveiled a positive and statistically significant effect between CRM and firm performance with a pooled or combined effect size of 0.524 under a confidence level of 95% and a confidence interval with a lower limit of 0.444 to an upper limit of 0.595, while the prediction interval of lower limit –0.239 to an upper limit of 0.887. The analysis showed high heterogeneity among the studies (I² = 97.25%) and indicated variability in terms of the effectiveness of CRM interventions across different contexts. Practical Implications : As the results indicated, policymakers could adopt innovative CRM strategies for better firm performance without any hesitation. However, while formulating strategies, they should consider the level of publication bias and heterogeneity and pilot-test the strategy in their local environment. Originality/Value : The findings of this meta-analysis could serve as a benchmark for future research, allowing the replacement of mean effect sizes in null hypothesis testing. Future research should also explore sector-specific nuances in CRM and customer behavior, considering that foundational principles may differ across industries.